Keeping up alliances: multifaceted values of pottery in eighth- to seventeenth-century eastern Botswana as reconstructed by optical petrography. Issue 3 (3rd July 2019) - Wilmsen, Edwin; Killick, David; Denbow, James; Daggett, Adrianne; Thebe, Phenyo
ABSTRACT: Many sites with Zhizo, Leopard's Kopje and Khami pottery have been identified around the southern and eastern margins of Sowa Pan, eastern Botswana. This paper presents results of the analysis of sherds from the three largest such sites — Kaitshàa, Thabadimasego, Tora Nju — plus clay from 39 geological deposits. Sherd fabrics identified by optical petrography reveal that pots were made of clays from several lithological terrains. This suggests associations with other sites. We demonstrate a north-south axis of pottery vessel movements — and thus of people — beginning about AD 900–1000 and extending from sites in the Chobe-Zambezi waterveld along Sowa Pan to Kaitshàa and onward to the Kalahari margins at Bosutswe; a later east-west axis connected Tora Nju with Bosutswe and the Khami regional centre at Domboshaba. Identical sherd fabrics, plus specific vessel design parallels, firmly establish the existence of alliances between these sites. This entailed a network of affiliations between potters whereby each preserved their own socially relevant precepts of potting, including potter-ancestor dynamics, while adapting alterations in new contexts of potting praxis. Sherds should thus be seen in terms of alliances rather than as an indicator merely of commodity-exchange. Our study demonstrates, on the basis of vessel fabric rather than of decorative data, that such interactions routinely took place in Botswana from Zhizo times onward. This paper therefore adds independent insights into studies of social alliance maintenance and pottery style syncretism in pre-colonial southern Africa.